Solar solutions - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Many families own portable radios but use them very sparingly due to the high cost of dry cell batteries (which can cost theequivalent of three days' food). By converting existing radios to work from the sun, not only are running costs...